ANKK1/DRD2 Locus Variants Are Associated With Rimonabant Efficacy in Aiding Smoking Cessation: Pilot Data. (1st December 2011) - Wilcox, Charles S.; Noble, Ernest P.; Oskooilar, Nader
Abstract : Background: Polymorphism of the DRD2 gene (rs1800497), previously termed Taq1A, includes the A1 and A2 alleles. The A1 + genotype (A1/A1, A1/A2) has been associated with smoking dependence. The present study determined which polymorphism of the DRD2 gene had a salutary outcome in administration of rimonabant, a drug used in smoking cessation and obesity studies. Methods: Seventy-six (76) smokers enrolled into a double-blind, placebo-versus-rimonabant, 10-week smoking cessation drug trial. Subjects provided a blood sample to determine whether they had the DRD2 A1 + genotype (A1/A1, A1/A2) or the DRD2 A1 − genotype (A2/A2). Smoking cessation (or continuation) was monitored on a weekly basis with on-site carbon monoxide (CO) monitoring. Results: Smokers in the rimonabant A1 − group were significantly more successful in completely stopping smoking compared to subjects in the placebo A1 − group ( P < 0.05). However, there was no difference in smoking cessation when the rimonabant A1 + group was compared to the placebo A1 + group. With respect to quantified verifiable/objective smoking cessation outcomes, exhaled CO (parts per million) was monitored during each week of the study. The rimonabant A1 − group compared to the placebo A1 − group was quantifiably smoking less at weeks 5, 6, and 7 ( P < 0.05), at week 8 ( P < 0.01), and at weeks 9 and 10 ( P < 0.001). No significant difference was found in exhaled CO levels between rimonabant A1 + group and the placebo A1 + group in any of the weeks studied. Conclusions: These findings further support the rationale for incorporating genotyping into clinical trials, particularly smoking cessation trials. Rimonabant demonstrated early and sustained smoking cessation efficacy only in noncarriers of the A1 allele. These results also underscore the risks of heterogeneity contributing to type 2 errors, when analyzing (phase 2 or 3) data. The potential clinical, regulatory, and commercial benefits associated with expediting and enhancing drug development, vis-à-vis the integration of biomarkers in clinical research, is supported by our findings.